Katecheza kościoła w polsce wobec wyzwań nowej ewangelizacji - Tomasik, Piotr (Verbum Vitae, 2012)
The author shows both how to accept the reply proposed by the new evangelization which challenges the present and how to carry it out as part of various catechetical activities of the Church in Poland. First, through the analysis of fundamental papal documents, he determines the character of the new evangelization. Then, he presents a reply of the new evangelization to contemporary problems with reference to Lineamenta prepared for the Synod of Bishops in 2012. He also explains how the catechesis can merge with the new evangelization, and analyses the tasks of catechesis, as described in the General Directory for Catechesis and adapted to Polish conditions.